Advertising discourse in the Republic of Belarus: ontology of risks - Saladounikava, Tatiana V. (Journal of the Belarusian State University. Journalism, 2020)
The advertising discourse is presented in the spirit of the concept of J. Baudrillard as an institutional discourse focused not so much on the promotion of goods and services as on the formation of values and attitudes of the consumer society. In the context of the radical transformation of Belarusian society caused by the dynamics of the introduction of digital information technologies, the ontology of risks generated by social, commercial and political advertising is considered. It has been established that the risks of advertising communication are directly related to the peculiarity of modern society, which is based on the risk economy, the economy of high-tech and high-tech industries, characterized by the extreme degree of political, economic, technological, financial and environmental uncertainties and risks. Specific examples disclose the specifics of the formation and course of these risks. It was revealed that the risks posed by advertising communication are directly related to the increasing role of Internet technologies, the emergence of fundamentally new tools aimed at manipulating people, which leads to the destructuring of the social and political situation and to an increase in the index of political uncertainty. It has been proposed a risk typologisation based on the quality of the information provided (uncertain/distorted). In development of the Concept of National Security of the Republic of Belarus, it has been justified a competency-based approach to improving the human resources potential in the field of information security, as well as public administration, in the person of specialists with linguistic, engineering (in the field of artificial intelligence) and managerial competencies capable of recognizing and minimizing threats caused by any type of advertising discourse.